Wicket-Keeping in Cricket: A Literature Review. Issue 3 (September 2013) - MacDonald, Danielle; Cronin, John; Mills, Jason; Stretch, Richard
Cricket is unique in that three formats of the game, of varying duration and intensity are played at elite level; Test, One Day and Twenty20 (T20) cricket. The wicket-keeper is a vital member of the fielding side; the only player who could be involved with every delivery of the innings. Despite this, there is a paucity of literature on wicket-keeping, with most research having focused on fast bowling and batting. This review is principally concerned with identifying the performance demands associated with wicket-keeping and the conditioning of these cricketers. To appreciate the performance demands of wicket-keeping, an integrated approach has been taken where the mental, technical, physiological, physical and tactical requirements of wicket-keeping are discussed. From this information, recommendations are made and suggestions for future research detailed.